Auditory extinction and dichotic listening cv task in cerebral infarction preliminary report - Mauro Muszkat; J. Osmar Cardeal; Clemente I. Ribeiro de Almeida; Maria Inez Campos; Carlos J. Reis de Campos (Arquivos de Neuro-Psiquiatria)
Six stroke patients were studied using a dichotic listening¹ CV task, 4 with left hemisphere infarction, 2 with right hemisphere infarction. It was observed a «lesion--effect», a shift of hemisphere prevalence to the side opposite a brain lesion. The authors suggest that the lesion-effect can be explained by the auditory extinction phenomenon at the linguistic level.